A First look at communication theory - Griffin, Em; Ledbetter, Andrew ;Sparks, Glenn (New York, NY : McGraw Hill Education, 2019)
A Balanced Approach to Theory Selection. We've written A First Look for students who have no background in communication theory. It's designed for undergraduates enrolled in an entry-level course, regardless of the students' classification. The trend in the field is to offer students a broad introduction to theory relatively early in their program. But if a department chooses to offer its first theory course on the junior or senior level, the course will still be the students' first comprehensive look at theory, so the book will meet them where they are.
Overview -- Interpersonal communication -- Group and public communication -- Mass communication -- Cultural context -- Integration.
Includes index.
Keywords: COMMUNICATION PHILOSOPHY